Numerical methods using MATLAB - Mathews, John H. (Prentice-Hall, 1999)
Preliminaries. The solution of nonlinear equations f(x) = 0. The solution of linear systems AX = B. Interpolation and polynomial approximation. Curve fitting. Numerical differentiation. Numerical integration. Numerical optimization. Solution of differential equations. Solution of partial differential....